Compact and Versatile QEPAS-Based Sensor Box for Simultaneous Detection of Methane and Infrared Absorber Gas Molecules in Ambient Air - Zifarelli, Andrea; Menduni, Giansergio; Giglio, Marilena; Elefante, Arianna; Sukhinets, Anton; Sampaolo, Angelo; Patimisco, Pietro; Fangyuan, Sun; Chongwu, Wang; Wang, Qi Jie; Spagnolo, Vincenzo (Frontiers in Environmental Chemistry, 2022)
In this work we report on an innovative sensor box employing two acoustic detection modules connected in series for quartz-enhanced photoacoustic multi-gas detection. One detection module is coupled with an internal distributed-feedback quantum cascade laser (DFB-QCL) emitting at ~7.719 µm for methane (CH4) sensing, while the second module has been designed to be coupled with an external laser source targeting the absorption features of a specific gas molecule Mx exhibiting absorption features in the infrared spectral range. The sensor box can thus be employed for any application, depending on the CH4/Mx gas combination to be detected. The ~7.719 µm DFB-QCL also allowed water vapor monitoring. To demonstrate the sensor versatility, we report on the QEPAS-box environmental monitoring application by simultaneously detecting in air methane, which is a greenhouse gas, nitric oxide (NO), an ozone depleting substance, and water vapor. Sensitivity levels of 4.30 mV∙ppm-1 and 17.51 mV∙ppm-1 and minimum detection limits of 48 ppb and 11 ppb for methane and nitric oxide detection where achieved, respectively. The sensor box operation was tested by analysing ambient air. Average concentrations of ~ 1.73 ppm of CH4, ~ 0.134 ppm of NO and 1.8% of H2O were measured.